187 'The toll that it's taken:' perspectives of black men recovering from traumatic injury in Philadelphia. (5th May 2020) - Jacoby, Sara; Webster, Jessica; Twomey, Catalyst; Gebreyesus, Abeselom
Abstract : Statement of Purpose: For the majority of individuals who will survive trauma, healing and restoration is often a long-term process shaped by everyday socio-ecological exposures. The purpose of this analysis was to describe how Black men in Philadelphia perceived the long-term sequalae of their injuries and the influence of environmental and structural factors on recovery. Methods: 26 individuals, 12–36 months after injury, were re-recruited from a concluded cohort study which followed over 600 seriously injured Black men from admission to a trauma center in Philadelphia to three months after hospitalization. This sub-sample was generally representative of larger cohort by age, mechanism of injury, insurance status, income, and education. Focus group and individual qualitative interviews elicited perceptions of: long-term symptoms attributed to injury, influences on recovery, outstanding needs for support, and opportunities to extend current health and social resources. Interviews were audio-recorded, transcribed, organized in NVIVO, and analyzed using inductive-deductive thematic analysis. Results: Four overarching themes emerged. The first, 'you used to run' includes subthemes signifying the persistence of psychological distress, chronic pain, increased substance use, changes in sleep, and social isolation 12–36 months after injury. The second, 'where it happened, ' describes the impact of neighborhood recovery environments on traumatic stress, gun carrying, outdoor activity, and proximity to social networks. The third, 'in a hole, ' refers to post-injury changes in workforce participation, financial stability, and barriers to healthcare access. The fourth, 'should be somebody's job to help' included perceived needs for services that address workforce re-entry, psychological stress, healthcare access and peer group interaction. Conclusions: The perceptions of Black men in Philadelphia on their long-term recovery illustrates individual, environmental, and structural factors that can be targeted for tertiary prevention. Contributions to Injury and Violence Prevention Science: Qualitative evaluation of the effects of trauma can be used to identify pathways through which to diminish outcome disparities and their origins in the socio-ecological context of recovery.